Evaluation of the behaviour of reinforced concrete beams repaired with glass fibre reinforced polymer (GFRP) using a damage variable - Rafael Nunes da Cunha; Kevin Mendona Oliveira; Antnio Gabriel Lisboa Rego Brito; Camila de Sousa Vieira; David Leonardo Nascimento de Figueiredo Amorim (Fracture and Structural Integrity)
The use of fibre reinforced polymers (FRP) for increasing the strength of reinforced concrete (RC) structures became a usual method. FRP presents easy application and demands low space and provide significant strength increase. Usually, the decision for FRP use is made in terms of applied loads and deflections. However, such quantities can vary significantly depending on the characteristics of the structural element e.g. span, effective depth and concrete resistance. Therefore, this paper aims to present an alternative control variable to analyse the behaviour of RC beams repaired with glass fibre reinforced polymer (GFRP), called damage. Such damage variable accounts for concrete cracking and it was experimentally measured before and after the application of GFRP. Note that the application of GFRP increased the ultimate load for all repaired beams. The damage values of such beams also increased when collapse was reached. Furthermore, it was observed that the collapse mechanism shifted to shear and did not occurred the failure of the GFRP.